Green Innovation, Keunggulan Bersaing, Pemberdayaan Dan Kinerja Pemasaran UKM Kabupaten Buleleng - IDN Arta Jiwa; Gede Arnawa (Asosiasi Peneliti Manajemen Adat Indonesia, 2021)
Improving SME performance sourced from technology and resources that make it competitive advantage of innovation. SMEs with the support of empowerment programs, are expected to innovate based on local wisdom in order to have a competitive advantage so they can maintain future business performance. Innovative research on marketing performance is widely researched on a large business scale, however small businesses are still lacking. The research aims to explain the partial and simultaneous influence of green innovation, competitive advantage and empowerment on marketing performance. Quantitative research methods by taking data through questionnaires with a sample of 43 respondents, data analysis using multiple regression. The result is competitive advantage and empowerment have positive and significant effect on marketing performance, but green innovation has a negative and not significant effect on marketing performance. Simultaneously there is a positive and significant influence on green innovation, competitive advantage and empowerment on the marketing performance.